The Evolution of Federal Courts’ Healthcare Antitrust Analysis: Does the PPACA Spell the End to Hospital Mergers? - Collin Z. Groebe (Washington University Law Review, 2015)
Traditionally, hospital mergers were seen as a benefit to consumers. That is no longer the case. After years of nonprofit hospitals engaging in price inflation and misreporting charity care, new hospital mergers will be more heavily scrutinized. Specifically, the United States government has implemented policies that are intended to shrink the relevant market, separate hospital services into individual lines, and require more than a good faith standard for evidence of proposed efficiencies. These policies were created as a response to the findings in antitrust court cases that hospital executives were increasing prices as a monopolist. These cases have worked to discredit previous studies supporting the notion that nonprofit hospitals exhibit a lower association between market share and price. The resurgence of hospital merger cases in the federal courts combined with the PPACA provisions—namely, ACO implementation and redefined charity-care standards—will subject mergers to heightened scrutiny. Some damage has already been done in the hospital merger setting, but it is certain that, going forward, nonprofit hospitals no longer enjoy the same deference as before.
Keywords: Affordable Care Act; PPACA; Hospital mergers; Mergers; Nonprofit hospitals